Interventions to Improve Antibiotic Use in Hospitals with Different Levels of Complexity in Colombia: Findings from a Before-and-After Study and Suggestions for the Future - Martha Carolina Valderrama-Rios; Carlos Arturo Álvarez-Moreno; Jorge Alberto Cortes (MDPI AG, 2023)
Background: In the collaborative efforts to control bacterial antimicrobial resistance (AMR), the challenge for many low- and middle-income countries currently lies in the adequate design and successful implementation and operation of different strategies aimed at improving antibiotic use during hospital care. This study aims to provide data on these different strategies in three hospitals with different levels of complexity and geographic locations in Colombia. Methods: This before-and-after study describes and analyzes the development and implementation of clinical practice guidelines (CPGs), continuing education courses, quick consultation tools, and antimicrobial stewardship programs (ASPs) with the use of telemedicine. This includes measuring indicators in the ASP framework such as adherence to CPGs and antibiotic consumption. Results: We used five CPGs developed in the Colombian context. We designed and developed a Massive Open Online Course (MOOC) and a mobile application (app) as strategies for dissemination and implementation. The ASP was designed and implemented according to each institution's level of complexity. In the three hospitals, a progressive increase in adherence to the antibiotic recommendations proposed in the CPGs was observed, and there was a lower use of antibiotics with the ASPs, both in the general wards and ICUs. Conclusions: We concluded that in medium-complexity hospitals located in small rural cities, successful development of ASPs is possible when they are well-planned, implemented, and supported by the organization. It is necessary that Colombia and other Latin American countries continue activities that reduce AMR by designing, implementing, and improving these interventions throughout the national territory.